Herbal soaps and creams - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Disabled and able-bodied people in Uganda are growing medicinal plants and making medicinal soaps and skin products.